A method for extracting bromine from brine
By using the D301 macropore weak alkaline anion exchange resin column, acidified quartz sand column and mixed exchange resin column during bromine extraction, combined with the ionization effect of acidified white carbon black, the problem of inefficient extraction in the prior art is solved, and the efficient and low-cost bromine extraction effect is achieved.
Patent Information
- Application Number
- CN202411707216.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing bromine extraction method has a low extraction rate of underground brine with a bromine content of less than 150 ppm, and the equipment covers a large area, has large equipment investment and high energy consumption, making it difficult to adapt to the decline in underground brine resources and changes in refining demand.
By ion exchange method, D301 large-pore weak alkaline anion exchange resin column, acidified quartz sand column and mixed exchange resin column are adsorbed sequentially, combined with the ionization effect of acidified white carbon black, the adsorption speed and efficiency of bromine are improved, and the efficient extraction of bromine is achieved through multiple oxidation and elution steps.
It has achieved efficient extraction of underground brine with a bromine content of less than 150ppm, with an extraction rate of 89.71-90.79%. The equipment covers a small area, small equipment investment and low energy consumption, making it suitable for industrial applications.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bromine extraction, and in particular to a method for extracting bromine from brine. Background Art
[0002] Bromine is the only non-metallic element that is liquid at room temperature. It is a dark reddish brown liquid with a pungent odor. As an important chemical raw material, bromine is widely used in flame retardants, medicines, pesticides, dyes, rubber and other fields.
[0003] Most of the bromine produced in my country is extracted from seawater or brine. Compared with seawater, brine has a higher bromine content and is easier to extract. However, with the exploitation of underground brine, the reserves of underground brine resources have decreased, and the bromine content in underground brine has also been declining. The bromine content in underground brine in some areas has been reduced from 300ppm to below 150ppm. The existing bromine extraction method is mainly the air blowing method, which specifically involves acidifying the brine, introducing chlorine gas for oxidation, using air to blow out free bromine, and then using an absorbent to absorb the blown free bromine to obtain an absorbent that has absorbed free bromine, and then distilling and condensing the absorbent that has absorbed free bromine to obtain bromine. During the air blowing method, the extraction efficiency of the air blowing method is greatly affected by the ambient temperature due to the great influence of temperature on the solubility of bromine. Moreover, during the blowing, the concentration of free bromine has a great influence on the blowing efficiency. Therefore, the air blowing method is mainly suitable for brine with a bromine content of 2-4g / L. For underground brine with a bromine content of less than 150ppm, the extraction rate is low, resulting in a large waste of brine resources. In addition, the air blowing method also has the disadvantages of large equipment footprint, large equipment investment, and high energy consumption, which further limits the application of the air blowing method. Therefore, it is an urgent problem to study a bromine extraction method that can be used for underground brine with a bromine content of less than 150ppm, with little influence of temperature on the extraction rate, small equipment footprint, small equipment investment, and low energy consumption.
[0004] Existing bromine extraction methods also include ion exchange method, liquid membrane method, gas membrane method, solvent extraction method, etc. Among them, the ion exchange method specifically involves filtering and acidifying the brine, then introducing an oxidant for oxidation to obtain oxidized brine, which contains free bromine, and then using a strongly alkaline quaternary ammonium anion exchange resin to adsorb the free bromine in the oxidized brine to obtain a bromine-loaded resin. During adsorption, the exchange groups in the strongly alkaline quaternary ammonium salt anion exchange resin fix the free bromine in the form of polyhalide anions, and then using a reducing agent to reduce the bromine-loaded resin to obtain bromide ions, and then using hydrochloric acid to elute the bromine-loaded resin to obtain an eluent, which contains bromide ions. The eluted resin can be regenerated, and finally an oxidant is introduced into the eluent for oxidation, and then distillation and rectification are performed to obtain bromine. The ion exchange method has the advantage of being less affected by temperature. Specifically, when the ambient temperature is in the range of 0-60°C, the temperature has little effect on the adsorption capacity of the strong alkaline quaternary ammonium anion exchange resin for free bromine, and the concentration of free bromine has little effect on the adsorption capacity of the strong alkaline quaternary ammonium anion exchange resin for free bromine. For underground brine with a bromine content of less than 150ppm, a relatively high extraction rate can still be achieved. In addition, the ion exchange method has a small equipment footprint, small equipment investment, and low energy consumption, and has broad application prospects in the field of bromine extraction from underground brine with low bromine content.
[0005] Basic research on the application of 201×7 strong basic anion exchange resin in the adsorption of bromine in concentrated seawater, Zhang Nahui, master's thesis of Zhejiang University of Technology, 2009 disclosed a method for extracting bromine from concentrated seawater by ion exchange. For concentrated seawater with an initial concentration of 127.8μg / mL, the free rate of bromine in concentrated seawater after oxidation can reach 95%, the static adsorption rate of bromine in concentrated seawater using 201×7 strong basic anion exchange resin can reach 93%, and the reduction rate of bromide ions in bromine-loaded resin using sodium sulfite can reach 97.9%. Therefore, for underground brine with a bromine content of less than 150ppm, a higher extraction rate can be achieved by ion exchange. However, in this study, there are the following two problems: First, due to the ion exchange rate of the 201×7 strong basic anion exchange resin on the surface of the 201×7 strong basic anion exchange resin when adsorbing bromine in concentrated seawater, The influence of the degree and the diffusion rate of ions inside the 201×7 strong basic anion exchange resin. For underground brine with low bromine content, as the 201×7 strong basic anion exchange resin adsorbs bromine, the mutual repulsion between the same charges in the 201×7 strong basic anion exchange resin is large, and the mutual repulsion between the same charges in underground brine with low bromine content is small, resulting in slow adsorption speed and low adsorption rate. This research is only in the laboratory stage, and during adsorption, in order to ensure complete adsorption, a longer adsorption time or a lower flow rate is used, and no scale-up experiment is carried out. After the scale-up experiment, as the flow rate increases, the adsorption rate will further decrease, further affecting the extraction rate; second, the 201×7 strong basic anion exchange resin is easily contaminated by organic matter, resulting in pore blockage and difficulty in regeneration. Specifically, the adsorption performance of the 201×7 strong basic anion exchange resin decreases significantly after multiple regenerations. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for extracting bromine from brine, which is less affected by temperature and can still achieve a relatively high extraction rate for underground brine with a bromine content of less than 150 ppm. In addition, the equipment occupies a small area, has a small equipment investment, and has low energy consumption. After an enlarged experiment, it still has a relatively high extraction rate, and the adsorption performance of the adsorption exchange resin used decreases slightly after multiple regenerations.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0008] A method for extracting bromine from brine, comprising the following steps: acidification, primary oxidation, impurity removal, preparation of acidified quartz sand filter material, preparation of acidified white carbon black, mixing, preparation of adsorption device, adsorption, reduction, elution, secondary oxidation, and treatment;
[0009] The acidification comprises filtering the underground brine, stirring the filtrate at a stirring speed of 200-300 rpm at room temperature, and adding a sulfuric acid aqueous solution to adjust the pH to 3-3.1 to obtain acidified underground brine;
[0010] The underground brine has a bromine content of 135 ppm;
[0011] The molar concentration of the aqueous sulfuric acid solution is 1-1.2 mol / L;
[0012] The addition rate of the aqueous sulfuric acid solution is 9-10 mL / min;
[0013] The primary oxidation comprises stirring the acidified underground brine at a stirring speed of 200-300 rpm at room temperature, and introducing chlorine gas to an oxidation potential of 1040-1080 mV to obtain the primary oxidized underground brine;
[0014] The chlorine gas is introduced at a rate of 10-15 mL / min;
[0015] The impurity removal is composed of the following steps: impurity removal with a strong basic anion exchange resin and impurity removal with a weak basic anion exchange resin;
[0016] The strong basic anion exchange resin is impurity-removed by completely immersing the 201×7 strong basic anion exchange resin in deionized water, standing at room temperature for 25-30 hours, filtering, washing the filter residue with deionized water for 3-4 times, and then completely immersing it in a hydrochloric acid aqueous solution, standing at room temperature for 14-16 hours, filtering, washing the filter residue with deionized water for 4-6 times, and then completely immersing it in a sodium hydroxide aqueous solution, standing at room temperature for 14-16 hours, filtering, and washing the filter residue with deionized water for 4-6 times to obtain the 201×7 strong basic anion exchange resin after impurity removal;
[0017] In the strong basic anion exchange resin impurity removal, the usage ratio of 201×7 strong basic anion exchange resin, deionized water, hydrochloric acid aqueous solution, and sodium hydroxide aqueous solution is 0.64-0.65kg:3.3-3.5L:3.3-3.5L:3.3-3.5L;
[0018] The 201×7 strong alkaline anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of quaternary amine, a chlorine-type ion form, a water content of 43%, a mass exchange capacity of 3.8 mmol / g, a wet true density of 1.10 g / mL, a wet apparent density of 0.71 g / mL, a ball rate of 96% after grinding, and an average particle size of 0.75 mm;
[0019] The weakly basic anion exchange resin is impurity-removed, and the D301 macroporous weakly basic anion exchange resin is completely immersed in deionized water, allowed to stand at room temperature for 25-30 hours, filtered, and the filter residue is rinsed with deionized water for 3-4 times, and then completely immersed in a hydrochloric acid aqueous solution, allowed to stand at room temperature for 14-16 hours, filtered, and the filter residue is rinsed with deionized water for 4-6 times, and then completely immersed in a sodium hydroxide aqueous solution, allowed to stand at room temperature for 14-16 hours, filtered, and the filter residue is rinsed with deionized water for 4-6 times to obtain the D301 macroporous weakly basic anion exchange resin after impurity removal;
[0020] In the weakly basic anion exchange resin impurity removal, the usage ratio of D301 macroporous weakly basic anion exchange resin, deionized water, hydrochloric acid aqueous solution, and sodium hydroxide aqueous solution is 0.28-0.3kg:2-2.5L:2-2.5L:2-2.5L;
[0021] The D301 macroporous weakly basic anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of tertiary amine, a chlorine-type ion form, a water content of 52%, a mass exchange capacity of 5.1 mmol / g, a wet true density of 1.05 g / mL, a wet apparent density of 0.70 g / mL, a ball rate of 95% after grinding, and an average particle size of 0.77 mm;
[0022] In the strong base anion exchange resin impurity removal and the weak base anion exchange resin impurity removal, the molar concentration of the hydrochloric acid aqueous solution is 1-1.2 mol / L, and the molar concentration of the sodium hydroxide aqueous solution is 1-1.2 mol / L;
[0023] The method for preparing the acidified quartz sand filter material comprises the following steps: hydroxylation, silanization, and hydrogen peroxide oxidation;
[0024] The hydroxylation is performed by completely immersing the quartz sand filter material in acetone, standing at room temperature for 14-16 hours, filtering, and then completely immersing the filter residue in a sodium hydroxide aqueous solution, standing at room temperature for 14-16 hours, filtering, washing the filter residue with deionized water for 4-6 times, and vacuum drying to obtain a hydroxylated quartz sand filter material;
[0025] In the hydroxylation, the usage ratio of quartz sand filter material, acetone, and sodium hydroxide aqueous solution is 0.28-0.3 kg: 2-2.5 L: 2-2.5 L;
[0026] The average particle size of the quartz sand filter material is 0.85 mm;
[0027] The molar concentration of the sodium hydroxide aqueous solution is 2.5-3 mol / L;
[0028] The silanization in the preparation of the acidified quartz sand filter material comprises mixing the hydroxylated quartz sand filter material, 3-mercaptopropyltrimethoxysilane and toluene, stirring and refluxing at 80-90° C. at a stirring speed of 50-100 rpm for 10-12 hours, filtering, washing the filter residue with toluene for 3-4 times, and vacuum drying to obtain the silanized quartz filter material;
[0029] The usage ratio of the quartz sand filter material in the hydroxylation to the 3-mercaptopropyltrimethoxysilane and toluene in the silanization in the preparation of the acidified quartz sand filter material is 0.28-0.3kg:0.06-0.07kg:3-3.5L;
[0030] The hydrogen peroxide in the preparation of the acidified quartz sand filter material is oxidized, and the silane quartz filter material and the hydrogen peroxide aqueous solution are mixed, stirred at room temperature at a stirring speed of 50-100 rpm for 24-26 hours, filtered, and the filter residue is rinsed with deionized water for 3-4 times, and vacuum dried to obtain the acidified quartz sand filter material;
[0031] The ratio of the amount of the quartz sand filter material in the hydroxylation to the amount of the aqueous hydrogen peroxide solution in the hydrogen peroxide oxidation in the preparation of the acidified quartz sand filter material is 0.28-0.3 kg: 3-3.5 L;
[0032] In the hydrogen peroxide oxidation in the preparation of the acidified quartz sand filter material, the mass concentration of the hydrogen peroxide aqueous solution is 30%;
[0033] The method for preparing acidified white carbon black comprises the following steps: silylation and hydrogen peroxide oxidation;
[0034] In the silanization of the preparation of acidified silica, silica, 3-mercaptopropyltrimethoxysilane and toluene are mixed, stirred and refluxed at 80-90° C. at a stirring speed of 50-100 rpm for 10-12 hours, filtered, the filter residue is washed with toluene 3-4 times, and vacuum dried to obtain silanized silica;
[0035] In the silanization process for preparing the acidified silica, the amount ratio of silica, 3-mercaptopropyltrimethoxysilane and toluene is 0.04-0.05 kg: 0.04-0.06 kg: 3-3.5 L;
[0036] The white carbon black is precipitated white carbon black with an average particle size of 10 μm;
[0037] In the preparation of the acidified silica, hydrogen peroxide is oxidized, silanized silica and a hydrogen peroxide aqueous solution are mixed, stirred at room temperature at a stirring speed of 50-100 rpm for 24-26 hours, filtered, the filter residue is rinsed with deionized water for 3-4 times, and vacuum dried to obtain the acidified silica;
[0038] The ratio of the amount of white carbon black in the silanization in the preparation of the acidified white carbon black to the amount of the aqueous hydrogen peroxide solution in the hydrogen peroxide oxidation in the preparation of the acidified white carbon black is 0.04-0.05 kg: 3-3.5 L;
[0039] In the hydrogen peroxide oxidation in the preparation of the acidified white carbon black, the mass concentration of the hydrogen peroxide aqueous solution is 30%;
[0040] The mixing is to mix the impurity-removed 201×7 strong alkaline anion exchange resin, acidified white carbon black, and deionized water, stir at room temperature at a stirring speed of 50-100 rpm for 4-5 hours, filter, and vacuum dry to obtain a mixed exchange resin;
[0041] The usage ratio of the strong basic anion exchange resin in the impurity removal, the 201×7 strong basic anion exchange resin in the impurity removal, the white carbon black in the silanization in the preparation of the acidified white carbon black, and the deionized water in the mixing is 0.64-0.65kg:0.04-0.05kg:2.8-3L;
[0042] The preparation of the adsorption device comprises preparing an ion exchange column from the impurity-removed D301 macroporous weakly basic anion exchange resin to obtain a D301 macroporous weakly basic anion exchange resin column;
[0043] The acidified quartz sand filter material is made into a filter column to obtain an acidified quartz sand column;
[0044] The mixed exchange resin is made into an ion exchange column to obtain a mixed exchange resin column;
[0045] In the preparation adsorption device, the amount ratio of the D301 macroporous weakly basic anion exchange resin after impurity removal to the 201×7 strongly basic anion exchange resin used in the preparation, the quartz sand filter material used in the preparation of the acidified quartz sand filter material, and the 201×7 strongly basic anion exchange resin used in the preparation of the mixed exchange resin is 0.28-0.3kg:0.28-0.3kg:0.64-0.65kg;
[0046] The inner diameters of the D301 macroporous weakly alkaline anion exchange resin column, the acidified quartz sand column, and the mixed exchange resin column are all 50 mm;
[0047] The adsorption comprises the following steps: at room temperature, the underground brine after primary oxidation is sequentially passed through a D301 macroporous weakly basic anion exchange resin column, an acidified quartz sand column, and a mixed exchange resin column to obtain an adsorbed D301 macroporous weakly basic anion exchange resin column, an adsorbed acidified quartz sand column, and an adsorbed mixed exchange resin column;
[0048] The ratio of the underground brine in the acidification to the 201×7 strong basic anion exchange resin used in the preparation of the D301 macroporous weak basic anion exchange resin column is 10L:0.28-0.3kg;
[0049] The flow rate of the underground brine after the primary oxidation is 300-350 mL / min;
[0050] The reduction comprises the following steps: at room temperature, the sodium sulfite aqueous solution is sequentially passed through a D301 macroporous weakly basic anion exchange resin column after adsorption, an acidified quartz sand column after adsorption, and an exchange resin column after adsorption, and the sulfite concentration in the sodium sulfite aqueous solution to be discharged does not change any more, thereby obtaining a D301 macroporous weakly basic anion exchange resin column after reduction, an acidified quartz sand column after reduction, and an exchange resin column after reduction;
[0051] In the reduction, the molar concentration of the sodium sulfite aqueous solution is 1 mol / L;
[0052] The flow rate of the sodium sulfite aqueous solution is 20-22 mL / min;
[0053] The elution comprises the following steps: passing the hydrochloric acid aqueous solution through a reduced D301 macroporous weakly basic anion exchange resin column, a reduced acidified quartz sand column, and a reduced mixed exchange resin column in sequence at room temperature, and collecting the outflowing hydrochloric acid aqueous solution, wherein the outflowing hydrochloric acid aqueous solution does not contain bromine, using all the collected outflowing hydrochloric acid aqueous solutions as eluent, and separating the 201×7 strong basic anion exchange resin and acidified silica in the eluted mixed exchange resin column according to different particle sizes, regenerating the eluted D301 macroporous weakly basic anion exchange resin column and 201×7 strong basic anion exchange resin using a sodium hydroxide aqueous solution, regenerating the eluted acidified quartz sand column and acidified silica using a sulfuric acid aqueous solution, and then mixing the 201×7 strong basic anion exchange resin and acidified silica according to the method of the sixth mixing step and the seventh step of preparing an adsorption device to prepare an ion exchange column;
[0054] In the elution, the molar concentration of the hydrochloric acid aqueous solution is 2 mol / L;
[0055] The flow rate of the hydrochloric acid aqueous solution is 20-22 mL / min;
[0056] The secondary oxidation is performed by stirring the eluent at a stirring speed of 200-300 rpm at room temperature, and simultaneously introducing chlorine gas until the oxidation potential is 1040-1080 mV to obtain the eluent after secondary oxidation;
[0057] The chlorine gas is introduced at a rate of 10-15 mL / min;
[0058] In the treatment, the eluate after the secondary oxidation is distilled and rectified to obtain bromine.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] (1) The method for extracting bromine from brine of the present invention comprises the following steps: when extracting bromine by an ion exchange method, a D301 macroporous weakly basic anion exchange resin column, an acidified quartz sand column, and a mixed exchange resin column are used for sequential adsorption, wherein the D301 macroporous weakly basic anion exchange resin column can adsorb some impurities with negative charge in underground brine, and then the mixture passes through the acidified quartz sand column. On the one hand, the acidified quartz sand column can further adsorb organic impurities in underground brine. On the other hand, since the D301 macroporous weakly basic anion exchange resin column affects the hydrogen ion content in underground brine, which further affects the adsorption of bromine by the mixed exchange resin column, the acidified quartz sand column can ionize hydrogen ions to supplement hydrogen ions for underground brine. The organic impurities are gradually adsorbed by the D301 macroporous weakly basic anion exchange resin column and the acidified quartz sand column, thereby avoiding the clogging problem caused by concentrated adsorption. The mixed exchange resin in the mixed exchange resin column is 201×7 strong alkaline anion exchange resin after impurity removal. Resin is replaced to prepare a mixture of ion exchange column and acidified silica. During mixing, the acidified silica ionizes hydrogen ions and combines with the quaternary amine groups on the surface of the 201×7 strong basic anion exchange resin after impurities are removed, thereby obtaining a 201×7 strong basic anion exchange resin with a positive charge on the surface and an acidified silica with a negative charge on the surface, and the negatively charged acidified silica is coated on the surface of the 201×7 strong basic anion exchange resin with a positive charge. Then, in the adsorption process, bromine combines with the 201×7 strong basic anion exchange resin with a positive charge to form a negatively charged polyhalide. The negatively charged acidified silica can adsorb and transfer bromine to the surface of the 201×7 strong basic anion exchange resin, and can also promote the inward transfer of the negatively charged polyhalide through repulsive force, thereby increasing the adsorption rate of bromine. Even after the amplification experiment, the flow rate of the underground brine is increased, and the adsorption rate is still high, which further ensures a high bromine extraction rate.
[0061] (2) The method of extracting bromine from brine of the present invention can still achieve a high extraction rate for underground brine with a bromine content of less than 150 ppm, and still has a high extraction rate after a scale-up experiment. When 10 L of underground brine is continuously treated at room temperature of 25°C, the extraction rate of bromine can reach 89.71-90.79%;
[0062] (3) The method of extracting bromine from brine of the present invention is less affected by temperature. When 10L of underground brine is continuously treated at room temperature of 5°C, the extraction rate of bromine can reach 89.44-90.52%;
[0063] (4) The method of extracting bromine from brine of the present invention adopts an ion exchange method, which has a small equipment footprint, small equipment investment and low energy consumption;
[0064] (5) In the method for extracting bromine from brine of the present invention, the adsorption performance of the adsorption exchange resin used decreases slightly after multiple regenerations. When the resin is continuously reused and regenerated for the 30th time, the extraction rate of bromine can reach 88.97-90.13%. DETAILED DESCRIPTION
[0065] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0066] The room temperature in Examples 1-3 and Comparative Examples 1-2 was 25°C.
[0067] The calculation formula of the extraction rate of bromine in Example 1-3 and Comparative Example 1-2 is: [(mass of bromine obtained × mass purity) / (10L×135ppm / 1000)]×100%;
[0068] In the calculation formula of the bromine extraction rate, the unit of the mass of the obtained bromine is g.
[0069] Example 1
[0070] A method for extracting bromine from brine, specifically:
[0071] 1. Acidification: After filtering 10L of underground brine, the filtrate was stirred at room temperature at a stirring speed of 200rpm, and a sulfuric acid aqueous solution with a molar concentration of 1 mol / L was slowly added to adjust the pH to 3 to obtain acidified underground brine;
[0072] The underground brine has a bromine content of 135 ppm;
[0073] The addition rate of the aqueous sulfuric acid solution is 9 mL / min;
[0074] 2. Primary oxidation: continue to stir all the acidified underground brine obtained in step 1 at room temperature at a stirring speed of 200 rpm, and slowly introduce chlorine gas until the oxidation potential reaches 1040 mV to obtain primary oxidized underground brine;
[0075] The chlorine gas introduction rate is 10 mL / min;
[0076] 3. Impurity removal: 0.64 kg of 201×7 strong alkaline anion exchange resin was completely immersed in 3.3 L of deionized water, allowed to stand at room temperature for 25 h, filtered, and the filter residue was rinsed 3 times with deionized water, and then completely immersed in 3.3 L of a hydrochloric acid aqueous solution with a molar concentration of 1 mol / L, allowed to stand at room temperature for 14 h, filtered, and the filter residue was rinsed 4 times with deionized water, and then completely immersed in 3.3 L of a sodium hydroxide aqueous solution with a molar concentration of 1 mol / L, allowed to stand at room temperature for 14 h, filtered, and the filter residue was rinsed 4 times with deionized water to obtain the impurity-removed 201×7 strong alkaline anion exchange resin;
[0077] The 201×7 strong alkaline anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of quaternary amine, a chlorine-type ion form, a water content of 43%, a mass exchange capacity of 3.8 mmol / g, a wet true density of 1.10 g / mL, a wet apparent density of 0.71 g / mL, a ball rate of 96% after grinding, and an average particle size of 0.75 mm;
[0078] 0.28 kg of D301 macroporous weakly basic anion exchange resin was completely immersed in 2 L of deionized water, allowed to stand at room temperature for 25 h, filtered, and the filter residue was rinsed with deionized water for 3 times, and then completely immersed in 2 L of a hydrochloric acid aqueous solution with a molar concentration of 1 mol / L, allowed to stand at room temperature for 14 h, filtered, and the filter residue was rinsed with deionized water for 4 times, and then completely immersed in 2 L of a sodium hydroxide aqueous solution with a molar concentration of 1 mol / L, allowed to stand at room temperature for 14 h, filtered, and the filter residue was rinsed with deionized water for 4 times to obtain the D301 macroporous weakly basic anion exchange resin after impurity removal;
[0079] The D301 macroporous weakly basic anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of tertiary amine, a chlorine-type ion form, a water content of 52%, a mass exchange capacity of 5.1 mmol / g, a wet true density of 1.05 g / mL, a wet apparent density of 0.70 g / mL, a ball rate of 95% after grinding, and an average particle size of 0.77 mm;
[0080] 4. Preparation of acidified quartz sand filter media:
[0081] (1) Hydroxylation: 0.28 kg of quartz sand filter material was completely immersed in 2 L of acetone, allowed to stand at room temperature for 14 h, filtered, and then the filter residue was completely immersed in 2 L of a 2.5 mol / L sodium hydroxide aqueous solution, allowed to stand at room temperature for 14 h, filtered, and the filter residue was rinsed with deionized water 4 times, and vacuum dried to obtain a hydroxylated quartz sand filter material;
[0082] The average particle size of the quartz sand filter material is 0.85 mm;
[0083] (2) Silanization: All the hydroxylated quartz sand filter material prepared in the hydroxylation in step (1), 0.06 kg of 3-mercaptopropyltrimethoxysilane, and 3 L of toluene were mixed, and the mixture was stirred and refluxed at 80° C. at a stirring speed of 50 rpm for 10 h, filtered, and the filter residue was rinsed with toluene three times, and vacuum dried to obtain a silanized quartz filter material;
[0084] (3) Hydrogen peroxide oxidation: All the silanized quartz filter material prepared in the silanization step (2) and 3 L of a 30% aqueous hydrogen peroxide solution were mixed, stirred at room temperature at a stirring speed of 50 rpm for 24 h, filtered, and the filter residue was rinsed with deionized water for 3 times, and vacuum dried to obtain an acidified quartz sand filter material;
[0085] 5. Preparation of acidified white carbon black:
[0086] (1) Silanization: 0.04 kg of white carbon black, 0.04 kg of 3-mercaptopropyltrimethoxysilane and 3 L of toluene were mixed, stirred and refluxed at 80 ° C at a stirring speed of 50 rpm for 10 h, filtered, and the filter residue was rinsed with toluene 3 times, and vacuum dried to obtain silanized white carbon black;
[0087] The white carbon black is precipitated white carbon black with an average particle size of 10 μm;
[0088] (2) Hydrogen peroxide oxidation: all the silylated silica prepared in step (1) and 3 L of a 30% aqueous hydrogen peroxide solution were mixed, stirred at room temperature at a stirring speed of 50 rpm for 24 h, filtered, and the filter residue was rinsed with deionized water for 3 times, and vacuum dried to obtain acidified silica;
[0089] 6. Mixing: Mix all the impurity-removed 201×7 strong alkaline anion exchange resin obtained in step 3, all the acidified silica obtained in step 5, and 2.8 L of deionized water, stir at room temperature at a stirring speed of 50 rpm for 4 hours, filter, and vacuum dry to obtain a mixed exchange resin;
[0090] 7. Prepare an adsorption device: prepare an ion exchange column using all the impurity-free D301 macroporous weakly basic anion exchange resin obtained in the third step to obtain a D301 macroporous weakly basic anion exchange resin column;
[0091] All the acidified quartz sand filter material obtained in the preparation of the acidified quartz sand filter material in step 4 is made into a filter column to obtain an acidified quartz sand column;
[0092] The mixed exchange resins obtained in step 6 are used to prepare an ion exchange column to obtain a mixed exchange resin column;
[0093] The inner diameters of the D301 macroporous weakly alkaline anion exchange resin column, the acidified quartz sand column, and the mixed exchange resin column are all 50 mm;
[0094] 8. Adsorption: At room temperature, all the first-oxidized underground brine obtained in the first oxidation of step 2 is sequentially passed through a D301 macroporous weakly basic anion exchange resin column, an acidified quartz sand column, and a mixed exchange resin column, and the flow rate is controlled to be 300 mL / min to obtain an adsorbed D301 macroporous weakly basic anion exchange resin column, an adsorbed acidified quartz sand column, and an adsorbed mixed exchange resin column;
[0095] 9. Reduction: at room temperature, a sodium sulfite aqueous solution with a molar concentration of 1 mol / L is sequentially passed through a D301 macroporous weakly basic anion exchange resin column after adsorption, an acidified quartz sand column after adsorption, and an adsorbed mixed exchange resin column, and the flow rate is controlled to be 20 mL / min, and the sulfite concentration in the sodium sulfite aqueous solution to be discharged does not change any more, to obtain a reduced D301 macroporous weakly basic anion exchange resin column, a reduced acidified quartz sand column, and a reduced mixed exchange resin column;
[0096] 10. Elution: at room temperature, passing a hydrochloric acid aqueous solution with a molar concentration of 2 mol / L through a reduced D301 macroporous weakly basic anion exchange resin column, a reduced acidified quartz sand column, and a reduced mixed exchange resin column in sequence, controlling the flow rate to be 20 mL / min, and collecting the outflowing hydrochloric acid aqueous solution, until the outflowing hydrochloric acid aqueous solution does not contain bromine, using all the collected outflowing hydrochloric acid aqueous solutions as eluent, and separating the 201×7 strong basic anion exchange resin and acidified silica in the eluted mixed exchange resin column by different particle sizes, regenerating the eluted D301 macroporous weakly basic anion exchange resin column and 201×7 strong basic anion exchange resin with a sodium hydroxide aqueous solution, regenerating the eluted acidified quartz sand column and acidified silica with a sulfuric acid aqueous solution, and then mixing the 201×7 strong basic anion exchange resin and the acidified silica according to the method of the sixth mixing step and the seventh step of preparing an adsorption device to prepare an ion exchange column;
[0097] 11. Secondary oxidation: Stir all the eluate obtained in step 10 at room temperature at a stirring speed of 200 rpm, and slowly introduce chlorine gas until the oxidation potential reaches 1040 mV to obtain the secondary oxidized eluate;
[0098] The chlorine gas introduction rate is 10 mL / min;
[0099] 12. Treatment: Distill and rectify all the secondary oxidation eluate obtained in the secondary oxidation in step 11 to obtain bromine.
[0100] The mass of bromine obtained in this example is 1.213 g, the mass purity is 99.84%, and the extraction rate of bromine is 89.71%.
[0101] Example 2
[0102] A method for extracting bromine from brine, specifically:
[0103] 1. Acidification: After filtering 10L of underground brine, the filtrate was stirred at room temperature at a stirring speed of 250rpm, and a sulfuric acid aqueous solution with a molar concentration of 1.1mol / L was slowly added to adjust the pH to 3.05 to obtain acidified underground brine;
[0104] The underground brine has a bromine content of 135 ppm;
[0105] The addition rate of the aqueous sulfuric acid solution is 10 mL / min;
[0106] 2. Primary oxidation: Continue stirring all the acidified underground brine obtained in step 1 at room temperature at a stirring speed of 250 rpm, and slowly introduce chlorine gas until the oxidation potential reaches 1040 mV, to obtain primary oxidized underground brine;
[0107] The chlorine gas introduction rate is 12 mL / min;
[0108] 3. Impurity removal: 0.64 kg of 201×7 strong alkaline anion exchange resin was completely immersed in 3.4 L of deionized water, allowed to stand at room temperature for 28 h, filtered, and the filter residue was rinsed 3 times with deionized water, and then completely immersed in 3.4 L of a hydrochloric acid aqueous solution with a molar concentration of 1.1 mol / L, allowed to stand at room temperature for 15 h, filtered, and the filter residue was rinsed 5 times with deionized water, and then completely immersed in 3.4 L of a sodium hydroxide aqueous solution with a molar concentration of 1.1 mol / L, allowed to stand at room temperature for 15 h, filtered, and the filter residue was rinsed 5 times with deionized water to obtain the impurity-removed 201×7 strong alkaline anion exchange resin;
[0109] The 201×7 strong alkaline anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of quaternary amine, a chlorine-type ion form, a water content of 43%, a mass exchange capacity of 3.8 mmol / g, a wet true density of 1.10 g / mL, a wet apparent density of 0.71 g / mL, a ball rate of 96% after grinding, and an average particle size of 0.75 mm;
[0110] 0.29 kg of D301 macroporous weakly basic anion exchange resin was completely immersed in 2.2 L of deionized water, allowed to stand at room temperature for 28 h, filtered, and the filter residue was rinsed with deionized water for 3 times, and then completely immersed in 2.2 L of a hydrochloric acid aqueous solution with a molar concentration of 1.1 mol / L, allowed to stand at room temperature for 15 h, filtered, and the filter residue was rinsed with deionized water for 5 times, and then completely immersed in 2.2 L of a sodium hydroxide aqueous solution with a molar concentration of 1.1 mol / L, allowed to stand at room temperature for 15 h, filtered, and the filter residue was rinsed with deionized water for 5 times to obtain the D301 macroporous weakly basic anion exchange resin after impurity removal;
[0111] The D301 macroporous weakly basic anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of tertiary amine, a chlorine-type ion form, a water content of 52%, a mass exchange capacity of 5.1 mmol / g, a wet true density of 1.05 g / mL, a wet apparent density of 0.70 g / mL, a ball rate of 95% after grinding, and an average particle size of 0.77 mm;
[0112] 4. Preparation of acidified quartz sand filter media:
[0113] (1) Hydroxylation: 0.29 kg of quartz sand filter material was completely immersed in 2.2 L of acetone, allowed to stand at room temperature for 15 h, filtered, and then the filter residue was completely immersed in 2.2 L of a sodium hydroxide aqueous solution with a molar concentration of 2.8 mol / L, allowed to stand at room temperature for 15 h, filtered, and the filter residue was rinsed with deionized water for 5 times, and vacuum dried to obtain a hydroxylated quartz sand filter material;
[0114] The average particle size of the quartz sand filter material is 0.85 mm;
[0115] (2) Silanization: All the hydroxylated quartz sand filter material prepared in the hydroxylation in step (1), 0.06 kg of 3-mercaptopropyltrimethoxysilane, and 3.2 L of toluene were mixed, stirred and refluxed at 85° C. at a stirring speed of 80 rpm for 11 h, filtered, and the filter residue was rinsed with toluene three times, and vacuum dried to obtain a silanized quartz filter material;
[0116] (3) Hydrogen peroxide oxidation: All the silanized quartz filter material prepared in the silanization step (2) and 3.2 L of a 30% aqueous hydrogen peroxide solution were mixed, stirred at room temperature at a stirring speed of 80 rpm for 25 h, filtered, and the filter residue was rinsed with deionized water for 3 times, and vacuum dried to obtain an acidified quartz sand filter material;
[0117] 5. Preparation of acidified white carbon black:
[0118] (1) Silanization: 0.04 kg of white carbon black, 0.05 kg of 3-mercaptopropyltrimethoxysilane and 3.2 L of toluene were mixed, stirred and refluxed at 85 ° C at a stirring speed of 80 rpm for 11 hours, filtered, and the filter residue was rinsed with toluene for 3 times, and vacuum dried to obtain silanized white carbon black;
[0119] The white carbon black is precipitated white carbon black with an average particle size of 10 μm;
[0120] (2) Hydrogen peroxide oxidation: all the silylated silica prepared in step (1) and 3.2 L of a 30% aqueous hydrogen peroxide solution were mixed, stirred at room temperature at a stirring speed of 80 rpm for 25 h, filtered, and the filter residue was rinsed with deionized water for 3 times, and vacuum dried to obtain acidified silica;
[0121] 6. Mixing: Mix all the impurity-removed 201×7 strong alkaline anion exchange resin obtained in the impurity removal step 3, all the acidified silica obtained in the preparation of acidified silica in the step 5, and 2.9 L of deionized water, stir at room temperature at a stirring speed of 80 rpm for 4.5 h, filter, and vacuum dry to obtain a mixed exchange resin;
[0122] 7. Prepare an adsorption device: prepare an ion exchange column using all the impurity-free D301 macroporous weakly basic anion exchange resin obtained in the third step to obtain a D301 macroporous weakly basic anion exchange resin column;
[0123] All the acidified quartz sand filter material obtained in the preparation of the acidified quartz sand filter material in step 4 is made into a filter column to obtain an acidified quartz sand column;
[0124] The mixed exchange resins obtained in step 6 are used to prepare an ion exchange column to obtain a mixed exchange resin column;
[0125] The inner diameters of the D301 macroporous weakly alkaline anion exchange resin column, the acidified quartz sand column, and the mixed exchange resin column are all 50 mm;
[0126] 8. Adsorption: At room temperature, all the first-oxidized underground brine obtained in the first oxidation of step 2 is sequentially passed through a D301 macroporous weakly basic anion exchange resin column, an acidified quartz sand column, and a mixed exchange resin column, and the flow rate is controlled to be 320 mL / min to obtain an adsorbed D301 macroporous weakly basic anion exchange resin column, an adsorbed acidified quartz sand column, and an adsorbed mixed exchange resin column;
[0127] 9. Reduction: at room temperature, a sodium sulfite aqueous solution with a molar concentration of 1 mol / L is sequentially passed through a D301 macroporous weakly basic anion exchange resin column after adsorption, an acidified quartz sand column after adsorption, and an adsorbed mixed exchange resin column, and the flow rate is controlled to be 21 mL / min, and the sulfite concentration in the sodium sulfite aqueous solution to be discharged does not change any more, to obtain a reduced D301 macroporous weakly basic anion exchange resin column, a reduced acidified quartz sand column, and a reduced mixed exchange resin column;
[0128] 10. Elution: at room temperature, passing a hydrochloric acid aqueous solution with a molar concentration of 2 mol / L through a reduced D301 macroporous weakly basic anion exchange resin column, a reduced acidified quartz sand column, and a reduced mixed exchange resin column in sequence, controlling the flow rate to 21 mL / min, and collecting the outflowing hydrochloric acid aqueous solution, until the outflowing hydrochloric acid aqueous solution does not contain bromine, using all the collected outflowing hydrochloric acid aqueous solutions as eluent, and separating the 201×7 strong basic anion exchange resin and acidified silica in the eluted mixed exchange resin column by different particle sizes, regenerating the eluted D301 macroporous weakly basic anion exchange resin column and 201×7 strong basic anion exchange resin with a sodium hydroxide aqueous solution, regenerating the eluted acidified quartz sand column and acidified silica with a sulfuric acid aqueous solution, and then mixing the 201×7 strong basic anion exchange resin and the acidified silica according to the method of the sixth mixing step and the seventh step of preparing an adsorption device to prepare an ion exchange column;
[0129] 11. Secondary oxidation: Stir all the eluate obtained in step 10 at room temperature at a stirring speed of 250 rpm, and slowly introduce chlorine gas until the oxidation potential reaches 1040 mV to obtain a secondary oxidized eluate;
[0130] The chlorine gas introduction rate is 12 mL / min;
[0131] 12. Treatment: Distill and rectify all the secondary oxidation eluate obtained in the secondary oxidation in step 11 to obtain bromine.
[0132] The mass of bromine obtained in this example is 1.228 g, the mass purity is 99.81%, and the extraction rate of bromine is 90.79%.
[0133] Example 3
[0134] A method for extracting bromine from brine, specifically:
[0135] 1. Acidification: After filtering 10L of underground brine, the filtrate was stirred at room temperature at a stirring speed of 300rpm, and a sulfuric acid aqueous solution with a molar concentration of 1.2mol / L was slowly added to adjust the pH to 3.1 to obtain acidified underground brine;
[0136] The underground brine has a bromine content of 135 ppm;
[0137] The addition rate of the aqueous sulfuric acid solution is 10 mL / min;
[0138] 2. Primary oxidation: Continue stirring all the acidified underground brine obtained in step 1 at room temperature at a stirring speed of 300 rpm, and slowly introduce chlorine gas until the oxidation potential reaches 1080 mV to obtain primary oxidized underground brine;
[0139] The chlorine gas introduction rate is 15 mL / min;
[0140] 3. Impurity removal: 0.65 kg of 201×7 strong alkaline anion exchange resin was completely immersed in 3.5 L of deionized water, allowed to stand at room temperature for 30 h, filtered, and the filter residue was rinsed 4 times with deionized water, and then completely immersed in 3.5 L of a hydrochloric acid aqueous solution with a molar concentration of 1.2 mol / L, allowed to stand at room temperature for 16 h, filtered, and the filter residue was rinsed 6 times with deionized water, and then completely immersed in 3.5 L of a sodium hydroxide aqueous solution with a molar concentration of 1.2 mol / L, allowed to stand at room temperature for 16 h, filtered, and the filter residue was rinsed 6 times with deionized water to obtain the impurity-removed 201×7 strong alkaline anion exchange resin;
[0141] The 201×7 strong alkaline anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of quaternary amine, a chlorine-type ion form, a water content of 43%, a mass exchange capacity of 3.8 mmol / g, a wet true density of 1.10 g / mL, a wet apparent density of 0.71 g / mL, a ball rate of 96% after grinding, and an average particle size of 0.75 mm;
[0142] 0.3 kg of D301 macroporous weakly basic anion exchange resin was completely immersed in 2.5 L of deionized water, allowed to stand at room temperature for 30 h, filtered, and the filter residue was rinsed with deionized water 4 times, and then completely immersed in 2.5 L of a hydrochloric acid aqueous solution with a molar concentration of 1.2 mol / L, allowed to stand at room temperature for 16 h, filtered, and the filter residue was rinsed with deionized water 6 times, and then completely immersed in 2.5 L of a sodium hydroxide aqueous solution with a molar concentration of 1.2 mol / L, allowed to stand at room temperature for 16 h, filtered, and the filter residue was rinsed with deionized water 6 times to obtain the D301 macroporous weakly basic anion exchange resin after impurity removal;
[0143] The D301 macroporous weakly basic anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of tertiary amine, a chlorine-type ion form, a water content of 52%, a mass exchange capacity of 5.1 mmol / g, a wet true density of 1.05 g / mL, a wet apparent density of 0.70 g / mL, a ball rate of 95% after grinding, and an average particle size of 0.77 mm;
[0144] 4. Preparation of acidified quartz sand filter media:
[0145] (1) Hydroxylation: 0.3 kg of quartz sand filter material was completely immersed in 2.5 L of acetone, allowed to stand at room temperature for 16 h, filtered, and then the filter residue was completely immersed in 2.5 L of a 3 mol / L sodium hydroxide aqueous solution, allowed to stand at room temperature for 16 h, filtered, and the filter residue was rinsed with deionized water for 6 times, and vacuum dried to obtain a hydroxylated quartz sand filter material;
[0146] The average particle size of the quartz sand filter material is 0.85 mm;
[0147] (2) Silanization: All the hydroxylated quartz sand filter material prepared in the hydroxylation in step (1), 0.07 kg of 3-mercaptopropyltrimethoxysilane, and 3.5 L of toluene were mixed, and the mixture was stirred and refluxed at 90° C. at a stirring speed of 100 rpm for 12 h, filtered, and the filter residue was rinsed with toluene 4 times, and vacuum dried to obtain a silanized quartz filter material;
[0148] (3) Hydrogen peroxide oxidation: All the silanized quartz filter material prepared in the silanization step (2) and 3.5 L of a 30% aqueous hydrogen peroxide solution were mixed, stirred at room temperature at a stirring speed of 100 rpm for 26 h, filtered, and the filter residue was rinsed with deionized water for 4 times, and vacuum dried to obtain an acidified quartz sand filter material;
[0149] 5. Preparation of acidified white carbon black:
[0150] (1) Silanization: 0.05 kg of white carbon black, 0.06 kg of 3-mercaptopropyltrimethoxysilane and 3.5 L of toluene were mixed, stirred and refluxed at 90 ° C at a stirring speed of 100 rpm for 12 h, filtered, and the filter residue was rinsed with toluene 4 times, and vacuum dried to obtain silanized white carbon black;
[0151] The white carbon black is precipitated white carbon black with an average particle size of 10 μm;
[0152] (2) Hydrogen peroxide oxidation: all the silylated silica prepared in step (1) and 3.5 L of a 30% aqueous hydrogen peroxide solution were mixed, stirred at room temperature at a stirring speed of 100 rpm for 26 h, filtered, and the filter residue was rinsed with deionized water for 4 times, and vacuum dried to obtain acidified silica;
[0153] 6. Mixing: Mix all the impurity-removed 201×7 strong alkaline anion exchange resin obtained in the impurity removal step 3, all the acidified silica obtained in the preparation of acidified silica in the step 5, and 3 L of deionized water, stir at room temperature at a stirring speed of 100 rpm for 5 hours, filter, and vacuum dry to obtain a mixed exchange resin;
[0154] 7. Prepare an adsorption device: prepare an ion exchange column using all the impurity-free D301 macroporous weakly basic anion exchange resin obtained in the third step to obtain a D301 macroporous weakly basic anion exchange resin column;
[0155] All the acidified quartz sand filter material obtained in the preparation of the acidified quartz sand filter material in step 4 is made into a filter column to obtain an acidified quartz sand column;
[0156] The mixed exchange resins obtained in step 6 are used to prepare an ion exchange column to obtain a mixed exchange resin column;
[0157] The inner diameters of the D301 macroporous weakly alkaline anion exchange resin column, the acidified quartz sand column, and the mixed exchange resin column are all 50 mm;
[0158] 8. Adsorption: At room temperature, all the first-oxidized underground brine obtained in the first oxidation of step 2 is sequentially passed through a D301 macroporous weakly basic anion exchange resin column, an acidified quartz sand column, and a mixed exchange resin column, and the flow rate is controlled to be 350 mL / min to obtain an adsorbed D301 macroporous weakly basic anion exchange resin column, an adsorbed acidified quartz sand column, and an adsorbed mixed exchange resin column;
[0159] 9. Reduction: At room temperature, a sodium sulfite aqueous solution with a molar concentration of 1 mol / L is sequentially passed through a D301 macroporous weakly basic anion exchange resin column after adsorption, an acidified quartz sand column after adsorption, and an adsorbed mixed exchange resin column, and the flow rate is controlled to be 22 mL / min, and the sulfite concentration in the sodium sulfite aqueous solution to be discharged does not change, to obtain a reduced D301 macroporous weakly basic anion exchange resin column, a reduced acidified quartz sand column, and a reduced mixed exchange resin column;
[0160] 10. Elution: at room temperature, passing a hydrochloric acid aqueous solution with a molar concentration of 2 mol / L through a reduced D301 macroporous weakly basic anion exchange resin column, a reduced acidified quartz sand column, and a reduced mixed exchange resin column in sequence, controlling the flow rate to 22 mL / min, and collecting the outflowing hydrochloric acid aqueous solution, until the outflowing hydrochloric acid aqueous solution does not contain bromine, using all the collected outflowing hydrochloric acid aqueous solutions as eluent, and separating the 201×7 strong basic anion exchange resin and acidified silica in the eluted mixed exchange resin column by different particle sizes, regenerating the eluted D301 macroporous weakly basic anion exchange resin column and 201×7 strong basic anion exchange resin with a sodium hydroxide aqueous solution, regenerating the eluted acidified quartz sand column and acidified silica with a sulfuric acid aqueous solution, and then mixing the 201×7 strong basic anion exchange resin and the acidified silica according to the method of the sixth mixing step and the seventh step of preparing an adsorption device to prepare an ion exchange column;
[0161] 11. Secondary oxidation: Stir all the eluate obtained in step 10 at room temperature at a stirring speed of 300 rpm, and slowly introduce chlorine gas until the oxidation potential reaches 1080 mV to obtain a secondary oxidized eluate;
[0162] The chlorine gas introduction rate is 15 mL / min;
[0163] 12. Treatment: Distill and rectify all the secondary oxidation eluate obtained in the secondary oxidation in step 11 to obtain bromine.
[0164] The mass of bromine obtained in this example is 1.219 g, the mass purity is 99.82%, and the extraction rate of bromine is 90.13%.
[0165] Comparative Example 1
[0166] Based on the method for extracting bromine from brine in Example 2, the step of preparing acidified quartz sand filter material in step 4 is omitted; in the step of preparing the adsorption device in step 7, "making all the acidified quartz sand filter material obtained in the preparation of the acidified quartz sand filter material in step 4 into a filter column to obtain an acidified quartz sand column" is omitted; and the use of the quartz sand column is omitted in the adsorption step in step 8, the reduction step in step 9, and the elution step in step 10.
[0167] The remaining operations are the same as those in Example 1.
[0168] The mass of bromine obtained in this comparative example is 1.193 g, the mass purity is 99.84%, and the extraction rate of bromine is 88.23%.
[0169] Comparative Example 2
[0170] Based on the method for extracting bromine from brine in Example 2, the step 5 of preparing acidified silica and the step 6 of mixing are omitted, and in the step of preparing the adsorption device in step 7, "all the mixed exchange resins obtained in the mixing in step 6 are made into ion exchange columns to obtain a mixed exchange resin column" is changed to "all the impurity-free 201×7 strong alkaline anion exchange resins obtained in the impurity removal in step 3 are made into ion exchange columns to obtain a mixed exchange resin column".
[0171] The remaining operations are the same as those in Example 1.
[0172] The mass of bromine obtained in this comparative example is 0.924 g, the mass purity is 99.82%, and the extraction rate of bromine is 68.32%.
[0173] Test Example 1
[0174] The room temperature of Example 1-3 and Comparative Example 1-2 was changed from 25°C to 5°C, and the extraction rates of bromine obtained in Example 1-3 and Comparative Example 1-2 were as follows:
[0175]
[0176] Test Example 2
[0177] According to the methods of Example 1-3 and Comparative Example 1-2, the same D301 macroporous weakly basic anion exchange resin column, acidified quartz sand column, and mixed exchange resin column were reused and regenerated 30 times, each time treating 10L of underground brine with a bromine content of 135ppm. At the 30th time, the extraction rates of bromine obtained in Example 1-3 and Comparative Example 1-2 were as follows:
[0178]
[0179] From the extraction rates of bromine in Examples 1-3 and Comparative Examples 1-3, and the results of Test Examples 1 and 2, it can be seen that by adding an acidified quartz sand column to the D301 macroporous weakly basic anion exchange resin column and the mixed exchange resin column, the extraction rate of bromine and the extraction rate of bromine after repeated use and regeneration 30 times can be improved;
[0180] The extraction rate of bromine can be improved by mixing the impurity-removed 201×7 strong alkaline anion exchange resin with acidified white carbon black to prepare a mixed exchange resin.
[0181] Unless otherwise specified, all percentages used in the present invention are by mass.
[0182] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for extracting bromine from brine, characterized in that: The method comprises the following steps: acidification, primary oxidation, impurity removal, preparation of acidified quartz sand filter material, preparation of acidified white carbon black, mixing, preparation of adsorption device, adsorption, reduction, elution, secondary oxidation, and treatment; The method for preparing the acidified quartz sand filter material comprises the following steps: hydroxylation, silanization, and hydrogen peroxide oxidation; The hydroxylation comprises completely immersing the quartz sand filter material in acetone, standing at room temperature, filtering, and then completely immersing the filter residue in a sodium hydroxide aqueous solution, standing at room temperature, filtering, washing the filter residue with deionized water, and vacuum drying to obtain a hydroxylated quartz sand filter material; The silanization in the preparation of the acidified quartz sand filter material comprises mixing the hydroxylated quartz sand filter material, 3-mercaptopropyltrimethoxysilane and toluene, stirring and refluxing at 80-90° C., filtering, washing the filter residue with toluene, and vacuum drying to obtain the silanized quartz filter material; The hydrogen peroxide in the preparation of the acidified quartz sand filter material is oxidized, the silane quartz filter material and the hydrogen peroxide solution are mixed, stirred at room temperature, filtered, the filter residue is washed with deionized water, and vacuum dried to obtain the acidified quartz sand filter material; The method for preparing acidified white carbon black comprises the following steps: silylation and hydrogen peroxide oxidation; In the silylation in the preparation of acidified silica, silica, 3-mercaptopropyltrimethoxysilane and toluene are mixed, stirred and refluxed at 80-90° C. for 10-12 hours, filtered, the filter residue is washed with toluene, and vacuum dried to obtain silylated silica; In the preparation of the acidified silica, hydrogen peroxide is oxidized by mixing silylated silica and an aqueous solution of hydrogen peroxide, stirring at room temperature, filtering, washing the filter residue with deionized water, and vacuum drying to obtain the acidified silica; The mixing comprises mixing the impurity-removed 201×7 strongly basic anion exchange resin, acidified white carbon black, and deionized water, stirring at room temperature, filtering, and vacuum drying to obtain a mixed exchange resin; The preparation of the adsorption device comprises preparing an ion exchange column from the impurity-removed D301 macroporous weakly basic anion exchange resin to obtain a D301 macroporous weakly basic anion exchange resin column; The acidified quartz sand filter material is made into a filter column to obtain an acidified quartz sand column; The mixed exchange resin is made into an ion exchange column to obtain a mixed exchange resin column; The adsorption is carried out at room temperature by passing the underground brine after primary oxidation through a D301 macroporous weak alkaline anion exchange resin column, an acidified quartz sand column, and a mixed exchange resin column in sequence to obtain an adsorbed D301 macroporous weak alkaline anion exchange resin column, an adsorbed acidified quartz sand column, and an adsorbed mixed exchange resin column.
2. The method for extracting bromine from brine according to claim 1, characterized in that: The acidification comprises filtering the underground brine, stirring the filtrate at room temperature, and adding a sulfuric acid aqueous solution to adjust the pH to 3-3.1 to obtain acidified underground brine; The underground brine has a bromine content of 135 ppm; The molar concentration of the aqueous sulfuric acid solution is 1-1.2 mol / L; The addition rate of the aqueous sulfuric acid solution is 9-10 mL / min.
3. The method for extracting bromine from brine according to claim 1, characterized in that: The primary oxidation comprises stirring the acidified underground brine at room temperature, and introducing chlorine gas until the oxidation potential reaches 1040-1080 mV, to obtain the primary oxidized underground brine; The chlorine gas is introduced at a rate of 10-15 mL / min.
4. The method for extracting bromine from brine according to claim 1, characterized in that: The impurity removal is composed of the following steps: impurity removal with a strong basic anion exchange resin and impurity removal with a weak basic anion exchange resin; The strong basic anion exchange resin is impurity-removed by completely immersing 201×7 strong basic anion exchange resin in deionized water, allowing it to stand at room temperature, filtering, and washing the filter residue with deionized water, and then completely immersing it in a hydrochloric acid aqueous solution, allowing it to stand at room temperature, filtering, and washing the filter residue with deionized water, and then completely immersing it in a sodium hydroxide aqueous solution, allowing it to stand at room temperature, filtering, and washing the filter residue with deionized water to obtain the 201×7 strong basic anion exchange resin after impurity removal; In the strong basic anion exchange resin impurity removal, the usage ratio of 201×7 strong basic anion exchange resin, deionized water, hydrochloric acid aqueous solution, and sodium hydroxide aqueous solution is 0.64-0.65kg:3.3-3.5L:3.3-3.5L:3.3-3.5L; The 201×7 strong alkaline anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of quaternary amine, a chlorine-type ion form, a water content of 43%, a mass exchange capacity of 3.8 mmol / g, a wet true density of 1.10 g / mL, a wet apparent density of 0.71 g / mL, a ball rate of 96% after grinding, and an average particle size of 0.75 mm; The weakly basic anion exchange resin is impurity-removed by completely immersing the D301 macroporous weakly basic anion exchange resin in deionized water, allowing it to stand at room temperature, filtering, and washing the filter residue with deionized water, and then completely immersing it in a hydrochloric acid aqueous solution, allowing it to stand at room temperature, filtering, and washing the filter residue with deionized water, and then completely immersing it in a sodium hydroxide aqueous solution, allowing it to stand at room temperature, filtering, and washing the filter residue with deionized water to obtain the D301 macroporous weakly basic anion exchange resin after impurity removal; In the weakly basic anion exchange resin impurity removal, the usage ratio of D301 macroporous weakly basic anion exchange resin, deionized water, hydrochloric acid aqueous solution, and sodium hydroxide aqueous solution is 0.28-0.3kg:2-2.5L:2-2.5L:2-2.5L; The D301 macroporous weakly basic anion exchange resin has a skeleton of styrene-divinylbenzene, a functional group of tertiary amine, a chlorine-type ion form, a water content of 52%, a mass exchange capacity of 5.1 mmol / g, a wet true density of 1.05 g / mL, a wet apparent density of 0.70 g / mL, a ball rate of 95% after grinding, and an average particle size of 0.77 mm; In the impurity removal by the strong alkaline anion exchange resin and the impurity removal by the weak alkaline anion exchange resin, the molar concentration of the hydrochloric acid aqueous solution is 1-1.2 mol / L, and the molar concentration of the sodium hydroxide aqueous solution is 1-1.2 mol / L.
5. The method for extracting bromine from brine according to claim 1, characterized in that: In the hydroxylation, the usage ratio of quartz sand filter material, acetone, and sodium hydroxide aqueous solution is 0.28-0.3 kg: 2-2.5 L: 2-2.5 L; The average particle size of the quartz sand filter material is 0.85 mm; The molar concentration of the sodium hydroxide aqueous solution is 2.5-3 mol / L; The usage ratio of the quartz sand filter material in the hydroxylation to the 3-mercaptopropyltrimethoxysilane and toluene in the silanization in the preparation of the acidified quartz sand filter material is 0.28-0.3kg:0.06-0.07kg:3-3.5L; The ratio of the amount of the quartz sand filter material in the hydroxylation to the amount of the aqueous hydrogen peroxide solution in the hydrogen peroxide oxidation in the preparation of the acidified quartz sand filter material is 0.28-0.3 kg: 3-3.5 L; In the hydrogen peroxide oxidation for preparing the acidified quartz sand filter material, the mass concentration of the hydrogen peroxide aqueous solution is 30%.
6. The method for extracting bromine from brine according to claim 1, characterized in that: In the silanization process for preparing the acidified silica, the amount ratio of silica, 3-mercaptopropyltrimethoxysilane and toluene is 0.04-0.05 kg: 0.04-0.06 kg: 3-3.5 L; The white carbon black is precipitated white carbon black with an average particle size of 10 μm; The ratio of the amount of white carbon black in the silanization in the preparation of the acidified white carbon black to the amount of the aqueous hydrogen peroxide solution in the hydrogen peroxide oxidation in the preparation of the acidified white carbon black is 0.04-0.05 kg: 3-3.5 L; In the hydrogen peroxide oxidation in the preparation of the acidified white carbon black, the mass concentration of the hydrogen peroxide aqueous solution is 30%; The dosage ratio of the strong basic anion exchange resin 201×7 strong basic anion exchange resin in the impurity removal, the white carbon black in the silanization in the preparation of acidified white carbon black and the deionized water in the mixing is 0.64-0.65kg:0.04-0.05kg:2.8-3L.
7. The method for extracting bromine from brine according to claim 1, characterized in that: In the preparation adsorption device, the amount ratio of the D301 macroporous weakly basic anion exchange resin used in the preparation after the impurities are removed, the quartz sand filter material used in the preparation of the acidified quartz sand filter material, and the 201×7 strong basic anion exchange resin used in the preparation of the mixed exchange resin is 0.28-0.3kg:0.28-0.3kg:0.64-0.65kg; The inner diameters of the D301 macroporous weakly alkaline anion exchange resin column, the acidified quartz sand column, and the mixed exchange resin column are all 50 mm; The ratio of the underground brine in the acidification to the D301 macroporous weakly basic anion exchange resin used in the preparation of the D301 macroporous weakly basic anion exchange resin column is 10L:0.28-0.3kg; The flow rate of the underground brine after the primary oxidation is 300-350 mL / min.
8. The method for extracting bromine from brine according to claim 1, characterized in that: The reduction comprises the following steps: at room temperature, the sodium sulfite aqueous solution is sequentially passed through a D301 macroporous weakly basic anion exchange resin column after adsorption, an acidified quartz sand column after adsorption, and an exchange resin column after adsorption, and the sulfite concentration in the sodium sulfite aqueous solution to be discharged does not change any more, thereby obtaining a D301 macroporous weakly basic anion exchange resin column after reduction, an acidified quartz sand column after reduction, and an exchange resin column after reduction; In the reduction, the molar concentration of the sodium sulfite aqueous solution is 1 mol / L; The flow rate of the sodium sulfite aqueous solution is 20-22 mL / min.
9. The method for extracting bromine from brine according to claim 1, characterized in that: The elution comprises the following steps: passing the hydrochloric acid aqueous solution through a reduced D301 macroporous weakly basic anion exchange resin column, a reduced acidified quartz sand column, and a reduced mixed exchange resin column in sequence at room temperature, and collecting the outflowing hydrochloric acid aqueous solution, wherein the outflowing hydrochloric acid aqueous solution does not contain bromine, using all the collected outflowing hydrochloric acid aqueous solutions as eluent, and separating the 201×7 strong basic anion exchange resin and acidified silica in the eluted mixed exchange resin column according to different particle sizes, regenerating the eluted D301 macroporous weakly basic anion exchange resin column and 201×7 strong basic anion exchange resin using a sodium hydroxide aqueous solution, regenerating the eluted acidified quartz sand column and acidified silica using a sulfuric acid aqueous solution, and then mixing the 201×7 strong basic anion exchange resin and the acidified silica according to the mixing step and the step of preparing an adsorption device to prepare an ion exchange column; In the elution, the molar concentration of the hydrochloric acid aqueous solution is 2 mol / L; The flow rate of the hydrochloric acid aqueous solution is 20-22 mL / min.
10. The method for extracting bromine from brine according to claim 1, characterized in that: The secondary oxidation is performed by stirring the eluent at a stirring speed of 200-300 rpm at room temperature, and simultaneously introducing chlorine gas until the oxidation potential is 1040-1080 mV to obtain the eluent after secondary oxidation; The chlorine gas is introduced at a rate of 10-15 mL / min; In the treatment, the eluate after the secondary oxidation is distilled and rectified to obtain bromine.
Citation Information
Patent Citations
Preparation method for heatproof highly-basic anion exchange resin with great exchange capacity
CN105237666A
C3N4-Mt-SO3H composite material as well as preparation and application thereof
CN108187719A